Implementation of an interprofessional medication adherence program for HIV patients: description of the process using the framework for the implementation of services in pharmacy - Mélanie Lelubre; Olivier Clerc; Marielle Grosjean; Karim Amighi; Carine De Vriese; Olivier Bugnon; Marie-Paule Schneider (BMC, 2018)
Abstract Background The community pharmacy center of the Department of Ambulatory Care and Community Medicine of the Policlinique Médicale Universitaire (PMU), Lausanne, Switzerland developed and implemented an interprofessional medication adherence program for chronic patients (IMAP). In 2014, a project was launched to implement the IMAP for HIV patients in a public non-academic hospital with the collaboration of community pharmacists in the Neuchâtel area (Switzerland). This article aims to describe the different implementation stages and strategies of the project. Methods A posteriori description of the implementation process, including the conceptualization strategies and stages (exploration, preparation, operation, sustainability) using the Framework for the Implementation of Services in Pharmacy (FISpH). Results In 2014, an attending infectious disease physician and a nurse at a public hospital (Neuchâtel, Switzerland) contacted the PMU to implement the IMAP in their setting in collaboration with community pharmacies. Five volunteer community pharmacies in Neuchâtel were trained to deliver the program. Three factors were found to be essential to the successful launch and progress of the implementation project: the experience of the community pharmacy center of the PMU with the IMAP, the involvement of the PMU research team, and collaboration with an external start up (SISPha) to train and support pharmacists. During the operation stage, the most important strategy developed was that of regular meetings between all stakeholders. These allowed healthcare professionals to discuss the implementation progress, to address each stakeholder's expectations, and to exchange experiences to facilitate interprofessional collaboration and program delivery. Structural changes allowed the formalization of the activities at the hospital and in a community pharmacy. This formalization was identified as the transition step between the operation and the sustainability stages. Conclusions The transfer of the IMAP for HIV patients to a non-academic setting and its implementation are feasible. However, implementation of a new model of pharmacy service such as IMAP implies a deep change in practice. A transitional external support and the allocation of sufficient resources to carry out the IMAP are essential for its long-term sustainability.